PROACTIVE BEHAVIOR OF EMPLOYEES IN PAKISTAN’S HEALTH SECTOR: INVESTIGATING ITS ANTECEDENTS AND ORGANIZATIONAL OUTCOMES (PAKISTAN ISLAMICUS (An International Journal of Islamic & Social Sciences), 2024)
The proposed study's goal is to identify the consequences and antecedents of employees’ proactive behavior in Pakistan’s health sector. The Job Demands-Resources (JD-R) Theory delves into the workplace environment’s impact on both employee productivity and well-being. This study explores the ramifications of empowering leadership within the framework of the JD-R Theory through the administration of surveys and regression analysis through SPSS. Additionally, to examine our hypotheses, we employed the SPSS process macro for both Model 1 and Model 4. Our findings reveal a constructive connection between employees' proactive behavior and empowering leadership. Proactive behavior emerges as a pivotal factor in the model equation, as it is directly and positively linked to employees' task performance and their potential for career success. In our study, the intriguing moderator, namely psychological capital, acts as a powerful enhancer, further fortifying the connection between proactive behavior and empowering leadership, and attaining proactive behavior. In the realm of healthcare, the presence of proactive employees holds the key to bestowing a distinctive competitive edge upon organizations within the sector. Their proactive disposition and actions become instrumental in setting them apart from their industry rivals.